2021
DOI: 10.1111/gcb.15578
|View full text |Cite
|
Sign up to set email alerts
|

Physiological determinants of biogeography: The importance of metabolic depression to heat tolerance

Abstract: A quantitative understanding of physiological thermal responses is vital for forecasting species distributional shifts in response to climate change. Many studies have focused on metabolic rate as a global metric for analyzing the sublethal effects of changing environments on physiology. Thermal performance curves (TPCs) have been suggested as a viable analytical framework, but standard TPCs may not fully capture physiological responses, due in part to failure to consider the process of metabolic depression. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 179 publications
1
30
0
Order By: Relevance
“…Increases in metabolic rates to fuel rising maintenance costs can divert energy from other important processes (Sokolova et al, 2012). Alternatively, reducing metabolic rates via metabolic depression not only can be an energy‐saving mechanism during times of environmental stress but also results in reduced energy flow to important processes such as growth and reproduction (Guppy & Withers, 2007; Liao et al, 2021; Storey & Storey, 1990). We found that with exposure to both acute and chronic upwelling for M .…”
Section: Discussionmentioning
confidence: 99%
“…Increases in metabolic rates to fuel rising maintenance costs can divert energy from other important processes (Sokolova et al, 2012). Alternatively, reducing metabolic rates via metabolic depression not only can be an energy‐saving mechanism during times of environmental stress but also results in reduced energy flow to important processes such as growth and reproduction (Guppy & Withers, 2007; Liao et al, 2021; Storey & Storey, 1990). We found that with exposure to both acute and chronic upwelling for M .…”
Section: Discussionmentioning
confidence: 99%
“…Among the three small pelagic fishes, Japanese anchovy with the relatively high thermal optima and wide thermal niche range shows the highest stabilities in its RSI PCs, while chub mackerel with the intermediate thermal optima and thermal niche range has the lowest stability. The range (0.5) of μ and σ that is given in the sensitivity analyses could also be considered as a reference of individual differences for every individual from the same population may have different thermal optima and thermal niche ranges according to differences in their genetic expression, life histories, and habitats (Kim et al, 2020;King et al, 2018;Liao et al, 2021;Righton et al, 2010). Therefore, the high stability in RSI PCs with varying μ and σ may suggest consistency in responses to changing SST at individual levels, which make the responses easy to be detected at the stock or population levels.…”
Section: Responses Of Resource Abundance Indices To Rsi Pcsmentioning
confidence: 99%
“…Based on this framework, Gamliel et al (2020) incorporated physiology into species distribution models with focuses on projecting impact of warming on selected Mediterranean marine species, and they found incorporation of the physiological data led to less extreme range shift forecasts, indicating that climate-induced range shifts may be less drastic than previously predicted by only species distribution models that without considering physiological information. Similarly, Liao et al (2021) developed physiological species distribution models considering the physiological thermal safety margins of 26 species of intertidal mollusks and enabled better predictions about the relationship between thermal stress and species distributions. These studies emphasize that physiological data can provide valuable supplemental information for adjusting climateenvironment-biology relationships and update traditional understandings on climate-induced responses of marine organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Structural complexity of the habitat could provide microhabitat for intertidal species as "thermal refugia," and micro-scale physiological thermal tolerance can play an important role in determining whether species could survive in the face of extreme events (Li, Tan, et al, 2021;Lima et al, 2016). The accumulation of microscale physiological variations could enhance the macro-scale thermal resilience of intertidal species (Dong et al, 2017;Strain, Cumbo, et al, 2020), and thereby influence species distributional shifts affected by climate change (Bates et al, 2018;Li, Tan, et al, 2021;Liao et al, 2021;Schils & Wilson, 2006). At different time-scales, heat hardening can work synchronously with seasonal acclimatization to increase resistance of raze clam Sinonovacula constricta to high temperatures (Zhang et al, 2020(Zhang et al, , 2021.…”
Section: Post-settlement Establishment and Global Warmingmentioning
confidence: 99%
“…3. Species' response to global climate change has been verified to be largely determined by their physiological performance (Han et al, 2019;Liao et al, 2021). In order to accurately assess the impact of global climate change on the survival and distribution of intertidal macrobenthos, physiological tolerance of intertidal species at multiple spatiotemporal scales must be considered.…”
Section: Per S Pec Tive Smentioning
confidence: 99%